Estudo comparativo randomizado do tratamento da bexiga hiperativa com eletroestimulação vaginal e eletroestimulação transcutânea do nervo tibial posterior(PTNS) - BERQUÓ, Marcela Souza (2012)
INTRODUCTION: The overactive bladder syndrome (OAB) is a lower urinary tract pathology that negatively affects the quality of life (QOL) of women whose main symptom is your definition for urinary urgency, with or without incontinence usually accompanied by urinary frequency and nocturia in the absence of metabolic, infectious or local. The diagnosis of BH is defined from the clinical symptoms, but the voiding diary and urodynamic studies are good tools for objective evaluation of this pathology. There are several forms of treatment for OAB, are the main pharmacological and physical therapy, physical therapy has been being considered an important option in a clinical setting. OBJECTIVES: to do a systematic review article about physical therapy in the treatment of female miccional urgency, to evaluate and compare the effects, discomfort and improvement in quality of life (QOL) of vaginal electrostimulation and percutaneous tibial nerve stimulation (PTNS) in women with overactive bladder. METHODS: We conducted a comparative, prospective, randomized trial of physiotherapy in the sector of the Hospital Materno Infantil (HMI) in Goiânia-GO, from march 2010 to august 2011. We randomized 40 women with urodynamic diagnosis of detrusor overactivity, mixed incontinence with predominant symptoms of overactive bladder or urinary urgency only in two groups: vaginal electrical stimulation (n=20) and PTNS (n=20), being held 10 sessions in each group. We used urodynamic studies, voiding diary and QoL questionnaire of King's Health Questionnaire (KHQ) before and after the two procedures, and then visual analog scale. Statistical analysis used: Fisher exact tests, chi quadratic, U Mann Whitney and Wilcoxon tests with a significance level of 0.05. RESULTS: In voiding diary was a reduction in urinary frequency, urge incontinence, nocturia and urgency in both groups. The urgency was present in all women and disappeared in 90% in the PTNS group (p<0.001) and 80% in vaginal electrical stimulation (p<0.001). According to urodynamic evaluation, the group of vaginal electrostimulation showed disappearance of detrusor overactivity in 60% (p=0.005) and PTNS in 75% (p= 0.002). The urodynamics showed significant differences in some parameters analyzed within each specific group and to compare the two groups was not observed differences. The scale and the KHQ domains of the two procedures had similar results as physical therapy to improve QOL, but no significant difference between them. In relation to the discomfort of procedures, PTNS in 80% of women reported no discomfort and 80% reported vaginal electrostimulation mild to moderate discomfort (p<0.001). CONCLUSION: There was no significant difference in the effects and QOL between the vaginal electrical stimulation and PTNS. The PTNS promoted less discomfort for women.